Manajemen Lingkungan Masyarakat Melalui Pendekatan Culture and Behavior di Pesisir Timur Sumatera Utara - A. Hadian Pratama Hamzah; Nurhasanah Nurhasanah (J-MAS (Jurnal Manajemen dan Sains), 2023)
Human activities on the environment are inseparable from the by-products in the form of waste, for example paper, plastic, metal, glass or glass are by-products of human activities on the environment. Solid waste control does not only cover the environment in urban areas but rural areas on the coast is a global issue that has not been resolved. One way that can be taken in dealing with solid waste in the environment is through a cultural approach and local community knowledge. This study aims to identify the local wisdom of the community called "Meresik" in the coastal environment of Tapak Kuda Village by measuring the level of community participation in solid waste management. the research conducted was descriptive interpretative in nature, the results of questionnaires and interviews were interpreted through data triangulation, samples were taken by random sampling of 60 people and 10 key figures interviewed, data were analyzed descriptively by presenting quantitative and descriptive data on waste control activities in the coastal village environment Tapak Kuda is called "Meresik", the abstinence value against the prohibition of throwing garbage in the sea area and mangrove forests is a form of violation of customary norms in the environment, the habit of using natural materials as containers is a written regulation carried out by the village head, the concentration of disposal sites is carried out in one place with sorting Types of garbage and village clean-up rituals on Friday (resik) are traditional village rituals in maintaining sanitation and soil fertility. The level of community participation is 75% in the high category. the local community of the Village realizes that the culture of resik has an important role in maintaining an environmental condition, environmental cleanliness and good sanitation are heavily influenced by Islamic religious views, as well as prevailing norms and values regarding local wisdom in solid waste management, the level of participation is in the high category this is done with the village working group scheme in the process of collecting, sorting, reducing and educating local wisdom in Tapak Kuda Village.